Does the COVID-19 Outbreak Constitute a Force Majeure Event? A Pandemic Impact on Construction Contracts - Seng Hansen (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2020)
The emergence of novel coronavirus disease 2019 (COVID-19) at the end of 2019 has transformed from an epidemic to a pandemic disaster. As of 12 April 2020, this outbreak has spread to more than 210 countries and territories and caused 108,837 deaths. The development of this outbreak has resulted in the closure of several major cities in the world (such as Wuhan, Daegu, and Manila) to country-wide lockdowns as observed in Italy and Malaysia. This also affects the construction sector as a labor-intensive industry. Force majeure has become one of the critical points of discussion, considering that this provision allows a contract party to hinder from fulfilling its obligations on the grounds that events are beyond a party’s control. Nevertheless, the application of this provision often faces challenges considering that in prior legal cases, the Courts tend to interpret this clause narrowly. Thus, it would be problematic when the force majeure clause does not include an epidemic outbreak as a force majeure event in the contract. This paper aims to explore the potential of the COVID-19 outbreak as a force majeure event in construction contracts. A qualitative approach consisting of two-step interdependent methods was done to highlight the fundamental elements of force majeure and to analyze whether the COVID-19 outbreak constitutes a force majeure event or not. Finally, a decision model was developed to assist the contracting parties in determining the COVID-19 outbreak potential as a force majeure event. This paper contributes since research related to the impacts of epidemic or pandemic outbreaks on the construction industry has not been intensified.